Syphilis Screening (Treponema pallidum bacteria) in Pregnant Women at Health Center Dosay Papua - Romadhonni, Tika; Rampa, Ester; Taroreh, Jannete Elisabeth; Sigalingging, Eldian; Sinaga, Herlando (Jurnal Biogenerasi, 2024)
Pregnant women are people who are in the process of fertilization to continue offspring. In the body of a pregnant woman, there is a fetus that grows in the womb. Pregnancy is an important period of life. A pregnant woman must prepare herself well so as not to cause problems with the health of the mother, baby, and during the birth process. The purpose of this study was to determine the results of syphilis examination in pregnant women at the Dosay Health Center. This type of research is a laboratory test with Rapid TP. The population used in this study were all pregnant women patients who came to check themselves at the Dosay Health Center. The number of samples in this study was 34 patients. The method of examining Syphilis in pregnant women at the Dosay Health Center is the Immunochromatographic method. the research time took place from June 14 to June 30, 2022, with the research location at the Dosay Health Center Laboratory. Based on the results of analysis and discussion, it can be concluded that of the 34 pregnant women respondents (100%) there were 4 respondents (11.8%) infected with syphilis (Treponema pallidum bacteria).